TRPC3 Is Dispensable for β-Alanine Triggered Acute Itch - Peter Dong (Nature Portfolio, 2017)
Abstract The detection of pruritic (itchy) stimuli is mediated by a variety of receptors and channels expressed by primary sensory neurons. The G protein-coupled receptor (GPCR) MRGPRD is selectively expressed by a subset of mouse non-peptidergic nociceptors and functions as the molecular receptor for the itch-inducing chemical β-alanine. However, the channels responsible for generating electrical signals downstream of MRGPRD remain unclear. Here, we found that a member of the canonical TRP channel family, TRPC3, is highly expressed in MRGPRD+ non-peptidergic nociceptors, raising the possibility of whether TRPC3 functions as a downstream channel in the MRGPRD signaling pathway. We tested TrpC3 null mice for β-alanine induced itch, and found that these mice exhibit normal responses to β-alanine. At the cellular level, calcium influx triggered by β-alanine is also unchanged in cultured DRG neurons from TrpC3 null mice compared to wild type. Together, our results demonstrate that mouse TrpC3 is dispensable for β-alanine-induced acute itch.